(untitled) (Web of Teachers: Inderscience Research, 2024)
Business is a complex process, and only a few business owners achieve success. According to statistics, 20% of business owners fail in their first year, 33% fail in their second year, and the businesses of 50% of surrounding entrepreneurs do not last beyond five years. The intense competition in such a situation often frustrates most entrepreneurs. Listening to the stories of those who have achieved success reveals qualities like perseverance, speed, quick decision-making, and the ability to analyze situations as critical for reaching the peak of success. In addition to these qualities, successful individuals also possess the ability to use the right words in the right place. A significant part of these words consists of phrases.